Spray drying and process optimization of the water treatment plant sludge - Sarti, A. [UNESP]; de Mello, B. S. [UNESP]; Rodrigues, B. C.G. [UNESP]; Costa, M. A.M. [UNESP]; Moruzzi, R. B. [UNESP]; de Oliveira, S. C. [UNESP] (Taylor & Francis, 2024)
In this study, a drying process by atomization was studied using a laboratory scale spray-dryer to define, through statistical techniques of experimental design, the best operational conditions for drying sludge from decanters and filters in water treatment plants (WTPs). A statistical methodology, based on a central composed rotational experimental design, was applied to a lab-scale spray-dryer (0.5 L/h) aiming to investigate the main independent variables that may interact with the drying process, specifically, on the final humidity of the powdered product (response variable). Feed solids concentration (0.44 – 3.22%), air flow rate (26 - 94 m3/h) and drying air temperature (133 - 217 ⁰C) were studied aiming to monitor and optimize the drying process. The results show that the proposed spray-drying process has great potential for reducing the humidity present in the sludge to minimum values (~ 1.5%), which may enable the application of this technology.